2015
DOI: 10.1016/j.jss.2015.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal alkaline phosphatase to treat necrotizing enterocolitis

Abstract: Background Intestinal alkaline phosphatase (IAP) activity is decreased in necrotizing enterocolitis (NEC), and IAP supplementation prevents NEC development. It is not known if IAP given after NEC onset can reverse the course of the disease. We hypothesized that enteral IAP given after NEC induction would not reverse intestinal injury. Materials and methods NEC was induced in Sprague–Dawley pups by delivery preterm followed by formula feedings with lipopolysaccharide (LPS) and hypoxia exposure and continued u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Importantly, oral ALPI supplementation protected ALPI-deficient mice from increased susceptibility to DSS-induced colitis (Ramasamy et al, 2011) and from chronic colitis induced by recurrent non-lethal infections by S. typhimurium (Yang et al, 2017). This treatment also significantly reduced intestinal inflammation in several mouse models of colitis and prevented LPS translocation (Ramasamy et al, 2011;Martínez-Moya et al, 2012;Rentea et al, 2012;Heinzerling et al, 2014;Biesterveld et al, 2015). Moreover, a small trial in patients with ulcerative colitis showed that administration of exogenous ALPI was not only well tolerated but also associated with short-term improvement in clinical scores (Lukas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, oral ALPI supplementation protected ALPI-deficient mice from increased susceptibility to DSS-induced colitis (Ramasamy et al, 2011) and from chronic colitis induced by recurrent non-lethal infections by S. typhimurium (Yang et al, 2017). This treatment also significantly reduced intestinal inflammation in several mouse models of colitis and prevented LPS translocation (Ramasamy et al, 2011;Martínez-Moya et al, 2012;Rentea et al, 2012;Heinzerling et al, 2014;Biesterveld et al, 2015). Moreover, a small trial in patients with ulcerative colitis showed that administration of exogenous ALPI was not only well tolerated but also associated with short-term improvement in clinical scores (Lukas et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Enteral barrier, local and systemic inflammation in an NEC model improved following IAP administration. 14,18,19 One important question remains as to whether the deficiency of IAP leads to an increased risk of NEC or whether NEC leads to decreased IAP expression. 37 Preterm rats have decreased expression of IAP when increased enteric inflammation ensues during NEC stressors.…”
Section: Discussionmentioning
confidence: 99%
“…17 Our previous research demonstrated that IAP is highly effective in the NEC in a rodent model, ameliorating enteral histologic injury, increasing enteral barrier function, and decreasing local and systemic inflammation. 14,[18][19][20] Expression of IAP is enterocyte differentiation dependent and IAP is regarded as a key enzyme when considering changes in the primary digestive and absorptive function. 21 While several regulators of IAP expression and transcription have been identified including cdx1 and cdx2, and Kruppel like factor 4, 22,23 it is unknown the impact that formula feeding and cesarean section have in the first few days of the neonatal rat model.…”
Section: Introductionmentioning
confidence: 99%
“…The neonates are generally supersensitive to the TLR ligands (31). The naïve intestinal epithelium of the neonates responds to TLR ligands (27, 28, 30), and these responses may play critical role in the pathogenesis of NEC (32-34, 61). Thus, Semapimod may prevent NEC by blocking TLR ligand signaling in the neonatal intestine.…”
Section: Discussionmentioning
confidence: 99%